Introduction to Blockchain for Azure developers (Apress, 2019)
"Understand the foundations of blockchain technologies such as Bitcoin and Ethereum, and learn the importance of blockchain for software developers in Microsoft Azure Cloud. This video introduces the basic concepts of cryptography used in blockchain and focuses on describing the popular blockchain platform Ethereum and how it is different from Bitcoin. It discusses the structure of a transaction, the cryptographic security involved, the prevention of double spending, and the consensus mechanism. Moving forward, you will go through examples of the architecture designs of blockchain solutions built on Azure along with common integration patterns in Azure Blockchain Workbench and the Blockchain API. Finally, you will see practical use cases of blockchain in the real world, including finance and capital investment markets, government, education, healthcare, supply chain, and energy. After watching the video, you will understand how blockchain works. You will also discover how blockchain can help optimize business processes and reduce operating costs, with practical implementations using Microsoft Azure Cloud as the delivery platform."--Resource description page